High voltage fragmentation and mechanical recycling of glass fibre thermoset composite. Issue 1 (2016) - Mativenga, Paul T.; Shuaib, Norshah A.; Howarth, Jack; Pestalozzi, Fadri; Woidasky, Jörg
Abstract: Global increase of composite waste urgently requires innovative recycling technology. The three dimensional cross-linked structure makes melting and remoulding of thermoset composite impossible. In this study, high voltage fragmentation, originally conceived for fracturing rocks was investigated as a potential process for composite recycling. It was then benchmarked against its competitor, mechanical recycling. The investigation covered effectiveness in separating composite phases, energy demand and recyclate quality. The work is a new contribution to the performance evaluation of key technologies for rapid recycling glass fibre thermoset composites, a major challenge for manufacturing and end-of-life product waste.